REKAYASA NILAI PEMBUATAN TERHADAP WAKTU DAN SPESIFIKASI PEKERJA PADA PEMBANGUNAN PERUMAHAN PESONA TUGU RANTE RESIDENCE TYPE 45 KABUPATEN BLITAR - Sugianto, Sugianto (Jurnal Qua Teknika, 2017)
due torecent economic situation, contractors have een required to be able to minimize cost and the same time to also maintain the quality of the project. One of the methods that can be apllied as an alternative to achieve it is value engineering. The aim of this studyis to apply this method in a construction project. The construction project ofHousing development in charm tugu rante type 45 residence district blitar Rp 99,792,000.00Value engineering method consist of 4 ( five ) phases. It covers information phase, which contains of identification of the high-cost work and the unnecessary cost ( function analysis ); creative phase; analyzing phase which includes the selection of alternative dealing with the analysis of its benefit and cost, it project life cycle cost and the selection of alternatives by using AHP method; and Recommendation phase.By implementing thismethod,the project cost can be minimized in 5 area of wark,woll work Rp1,902,459,wall strucco work Rp3,941,693,the work of the faundotion stone,soil excavation Rp211,616,excavation work Rp782,012,ceramic work Rp294,775. Thus total reduction cost that be achieved by using this method is upto